LRRK2 activation controls the repair of damaged endomembranes in macrophages. (9th July 2020) - Herbst, Susanne; Campbell, Philip; Harvey, John; Bernard, Elliott M; Papayannopoulos, Venizelos; Wood, Nicholas W; Morris, Huw R; Gutierrez, Maximiliano G
Abstract: Cells respond to endolysosome damage by either repairing the damage or targeting damaged endolysosomes for degradation via lysophagy. However, the signals regulating the decision for repair or lysophagy are poorly characterised. Here, we show that the Parkinson's disease (PD)‐related kinase LRRK2 is activated in macrophages by pathogen‐ or sterile‐induced endomembrane damage. LRRK2 recruits the Rab GTPase Rab8A to damaged endolysosomes as well as the ESCRT‐III component CHMP4B, thereby favouring ESCRT‐mediated repair. Conversely, in the absence of LRRK2 and Rab8A, damaged endolysosomes are targeted to lysophagy. These observations are recapitulated in macrophages from PD patients where pathogenic LRRK2 gain‐of‐function mutations result in the accumulation of endolysosomes which are positive for the membrane damage marker Galectin‐3. Altogether, this work indicates that LRRK2 regulates endolysosomal homeostasis by controlling the balance between membrane repair and organelle replacement, uncovering an unexpected function for LRRK2, and providing a new link between membrane damage and PD. Synopsis: Leucine‐rich repeat kinase 2 (LRRK2) has been linked to neurodegenerative and inflammatory diseases but it is unknown how LRKK2 activation occurs in these pathological conditions. Here, pathogen‐ or drug‐induced endomembrane damage is found to activate LRRK2 in macrophages, which in turn controls recruitment of membrane repair factors. LRRK2 is activated upon endomembrane damage. Endomembrane damage triggers LRRK2‐mediated phosphorylation of Rab8A. Rab8A and ESCRT component CHMP4B are recruited to damaged endolysosomes in a LRRK2‐dependent manner. In the absence of LRRK2 and Rab8A, damaged endolysosomes are disposed through lysophagy. Macrophages from patients harbouring LRRK2 G2019S or R1441C mutation show accumulation of damaged endolysosomes. Abstract : LRRK2 phosphorylation of Rab8A GTPase promotes its co‐translocation with ESCRT component CHMP4B to damaged endolysosomes for their repair.